Testing of paraffin oil efficiency against grape powdery mildew in Eger wine region - Pálfi, Xénia; Bisztray, Dénes; Villangó, Szabolcs; Pálfi, Zita; Deák, Tamás; Karácsony, Zoltán; Cseke, Gergely; Nagy, Péter; Zsófi, Zsolt (Acta Agraria Debreceniensis, 2016)
The aim of the present study was to examine the efficiency of paraffin oil against powdery mildew in Eger wine region. The experiment has been carried out in 2013 and 2014 with Chardonnay and Kékfrankos grape varieties, which have different resistance against powdery mildew. The effectiveness of the oil was examined on leaves and clusters (frequency and intensity). This oil was effective against Erysiphe necator infection on field trials in Chile and Brazil. The spread of downy mildew (Plasmopara viticola) was also inhibited by this material in some experiments conducted in Spain and France.The differences between oil treatments represented the sensitivity of the grape varieties in accordance with the applied dosages. The oil was effective against powdery mildew with different extent as a result of the so called ”vintage effect”. In 2013, the treatment of the highest dosage (D3) didn’t differed significantly in frequency and intensity of infection from the regular treatment (clusters of Kékfrankos, leaves of Chardonnay). In 2014, the oil was not so effective against powdery mildew compared to 2013. No remarkable differences were detected between the treatments due to the strong pressure of powdery mildew. Furthermore, no any effect of the lowest dosage (D1) was detected in the case of the sensitive clusters of Chardonnay and leaves of Kékfrankos in both experimental years.In summary, the oil treatment has an effect against powdery mildew, however this efficiency largely depends on the vintage characteristics and the pressure of powdery mildew. Further investigations are neccessary, for example field trials with combinations of other sprays. The oil can be useable as fungicide with proper care in eco-friendly integrated and bio (ecological) viticulture.